Selected metabolic changes after extreme endurance physical exercise by the example of marathon and ultra - marathon runners - Artur Uzdzicki; Malwina Malas; Tomasz Przybylski; Agnieszka Turoń-Skrzypińska; Aleksandra Szylinska; Zaneta Ciosek; Magdalena Ptak; Grazyna Dutkiweicz; Iwona Rotter (Kazimierz Wielki University, 2018)
A popularity of marathons and ultramarathons is growing every year. Attending a marathon can cause a variety of biochemical changes. It is crucial to determine which changes in blood tests are of clinical significance, and what recommendations should be given to the patient. Here the most frequent changes are presented, as described in literature.